ANALISIS KESALAHAN BERBAHASA INDONESIA PADA MAKALAH MAHASISWA PENDIDIKAN BAHASA INDONESIA UNIVERSITAS SILIWANGI ANGKATAN 2023: KAJIAN TATARAN SINTAKSIS - Dimas Hermawan; Nazwa Agnia Teja Respati; Dzikry Aqbil Rais; Roby Rahmat Kautsar; Iis Lisnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Language is an arbitrary system of sound symbols that is agreed upon and used by a group of society based on certain rules to communicate and interact in daily life. However in the practice of language use, errors in language are often still encountered especially in the use of Indonesian language. The purpose of research is to analyze Indonesian language errors in the papers of the Indonesian Languange Education students at Siliwangi University class of 2023 at the syntactic level. The method of research uses qualitative with a descriptive approach. Meanwhile, the data collection technique of research uses the read-note technique with the data analysis technique of research uses the Miles & Huberman model. The results and discussion of research indicate that there are errors in the papers of the Indonesian Languange Education students at Siliwangi University class of 2023 at the syntactic level. In the phrase structure there are 10 errors, in the clause structure there are 5 errors, and in the sentence structure there are 10 errors. Furthermore, hope of research can provide reflection and evaluation regarding errors in the Indonesian language, particularly at the syntactic level.